A Novel Photofragmentation of 1-Diphenylmethyl-3, 3- diphenyl-4-aryl / (2-thienyl)-2-azetidinones - Singh, G.S. (Asian Journal of Chemistry, 2010)
Photolysis of titled compounds 1-diphenylmethyl-3, 3-diphenyl-4-aryl/(2-thienyl)-2-azetidinones, (I) in dry benzene gave 1,4,4-triphenyl-5-aryl/(2-thienyl)-3-oxo-1,2,4,5-tetrahydrobenzazepins (II), 1,1,2,2-tetraphenylethane (III), diphenylmethane (IV) and arylnitriles (V). The products have been characterised on the basis of analytical and spectral (UV, IR, PMR and MS) data and the mechanistic route of their formation is suggested.